Improvement of sanitation facilities to achieve Sustainable Development Goals in Dusun 6 Desa Percut, Kecamatan Percut Sei Tuan (Talenta Publisher, 2020)
Sanitation problems have become a global concern. Indonesia is one of the countries with poor sanitation conditions because of the some community do not have access to proper sanitation. Poor sanitation has an impact on public health such as diarrhea, skin diseases and diseases from other vectors. Efforts to improve sanitation were made to realize the Sustainable Development Goals (SDGs) in the field of sanitation. This community service aims to build proper sanitation facilities for community on Dusun VI, Percut Village, Percut Sei Tuan district, conducted a test for ground water quality that used by community and provide a water pump to simplify process to get clean water and prevent contaminant. The construction of sanitation facilities are two bathrooms with a size of 2 x 1.5 m with closets in each room, a septic tank with a capacity of 20 people, repairing the terrace because the condition is not proper, testing the water quality for in situ parameter in site and ex situ parameters in the laboratory, and minimize contaminant in water sources by installing a water pump. This community service was able to provide proper sanitation facilities for 4 families and the quality of ground water still met the standards based on the minister of health regulation number No. 32 of 2017. Socialization to implemented healthy lifestyle by using sanitation fasilities properly should be done to increase public awareness of health and environment.